2020
DOI: 10.1371/journal.pone.0243842
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific effects on glycolysis by the dioxin-activated aryl hydrocarbon receptor

Abstract: Activation of the aryl hydrocarbon receptor (AHR) by the environmental toxin dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin, TCDD) causes diverse toxicities, including thymus atrophy and hepatosteatosis. The mechanisms by which AHR activation by TCDD leads to these toxicities are not fully understood. Here we studied the effects of TCDD on a major energy pathway, glycolysis, using the chick embryo close to hatching, a well-established model for studying dioxin toxicity. We showed that 24 hr of TCDD treatment caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Nonetheless, the details of the proteins and pathways involved in the regulation of AHR signalling activity are still far from complete and it might depend on features proper to each cellular context such as possible genetic mutations, exposure to exogenous cues and stage of cell differentiation ( 7 ). In here, we provide evidences that HK2 is a transcriptional target of AHR, as suggested by previous large-scale gene expression studies ( 22 , 57–59 ), and studies indicating that AHR might be an important regulator of glycolytic genes expression and glycolysis end-points ( 3 , 7 , 51 , 60–62 ). In MCF-7 cells, we identified a cluster of AHR binding sites in the vicinity of exon 3 of HK2 gene; and binding of AHR at the promoter of HK2 in two other cell lines GM17212 and HepG2.…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, the details of the proteins and pathways involved in the regulation of AHR signalling activity are still far from complete and it might depend on features proper to each cellular context such as possible genetic mutations, exposure to exogenous cues and stage of cell differentiation ( 7 ). In here, we provide evidences that HK2 is a transcriptional target of AHR, as suggested by previous large-scale gene expression studies ( 22 , 57–59 ), and studies indicating that AHR might be an important regulator of glycolytic genes expression and glycolysis end-points ( 3 , 7 , 51 , 60–62 ). In MCF-7 cells, we identified a cluster of AHR binding sites in the vicinity of exon 3 of HK2 gene; and binding of AHR at the promoter of HK2 in two other cell lines GM17212 and HepG2.…”
Section: Discussionsupporting
confidence: 82%
“…Several previous studies found that dioxin (TCDD) exposure can enhance glycolysis in an organ-specific manner as part of the toxic response. For instance, Moore et al observed that dioxin increased the mRNA levels of various glycolytic genes in the liver 66 . Wu et al also found that AMPK treatment significantly enhanced glycolysis as an adaptive response to oxidative stress in human skin fibroblasts 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Effects of TCDD were found to be organ specific leading to decreased glycolytic enzymes and glucose transporters in thymus and increased glycolytic enzymes and glucose transporters in liver. In TCDD-treated primary cultures of human hepatocytes glycolysis and GLUT1 were also increased (Diani-Moore et al 2020). These findings provide hints to molecular AHR targets of energy metabolism.…”
Section: Roles Of Cd38mentioning
confidence: 59%